Expected fiscal policy and interest rates in open economy - Salvatore Dell'Erba; Sergio Sola (Graduate Institute of International and Development Studies, 2011)
This paper reconsiders the long term effect of fiscal policy on interest rates using a real-time dataset of macroeconomic and fiscal variables in a panel of 17 OECD countries over the period 1989-2009. We show that, after controlling for cross sectional dependence using a Factor Augmented Panel, interest rates are mostly related to global factors. Among domestic fiscal variables, the level of expected public debt mantains a positive correlation with interest rates, while among the global factors, the aggregate monetary and fiscal stance play a quantitatively sizeable role. We then analyze how impulses from the aggregate fiscal stance influence each country's interest rates. We find that these effects are modest in large economies and particularly strong in economies characterized by low initial financial integration, leading the way to a novel interpretation of the divergent behaviour of interest rates in the recent financial crisis.
Keywords: C10; E43; F42; F62; H68; 330; Real time data; Fiscal Policy; Interest rates; Cross sectional dependence; Heterogeneous panels; Factor model; Finanzpolitik; Zins; Panel; Schätzung; OECD-Staaten